Electrolyte for ternary positive electrode silicon-carbon negative electrode lithium-ion battery and its application
By regulating the electrolyte components and adding specific film forming agents and coating agents to form a high-quality SEI film, the problem of short cycle life of ternary positive electrode silicon carbon negative electrode lithium-ion batteries is solved, and the effective maintenance of battery capacity and improvement of cycle performance is achieved.
Patent Information
- Application Number
- CN202510095585.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-22
AI Technical Summary
The current ternary positive electrode silicon-carbon negative electrode lithium-ion batteries have a short cycle life. The main factor is that the conventional electrolyte has poor matching between silicon-carbon negative electrodes, resulting in silicon expansion and breaking, consuming electrolyte, and rapidly reducing battery capacity.
By regulating the electrolyte components and distribution ratios of each group, the positive electrode film forming agent LiDFOB, the negative electrode composite film forming agent FEC and LiPO2F2, as well as the coating agents MBA and PST, a high-quality SEI film is formed to inhibit the volume expansion of silicon.
The cycle life of the ternary positive electrode silicon carbon negative electrode lithium-ion battery is extended, the battery capacity retention rate is improved, and the battery cycle performance is enhanced.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to an electrolyte for a ternary positive electrode silicon-carbon negative electrode lithium ion battery and its application. Background Art
[0002] In recent years, the new energy vehicle market has experienced explosive growth. As a high energy density, long life, and environmentally friendly battery technology, lithium-ion batteries have been widely understood and applied. As mid- to high-end new energy vehicle models are launched one after another, the cruising range has become an important parameter for the performance of new energy vehicles. Improving the specific energy of the battery is one of the ways to increase the cruising range of new energy vehicles.
[0003] Lithium-ion batteries are mainly composed of positive electrode materials, negative electrode materials, battery separators, electrolytes, and battery shells. Among them, positive electrode materials and negative electrode materials are the key components of lithium-ion batteries, which directly determine the specific energy of lithium-ion batteries. Ternary positive electrode materials have obvious advantages in specific energy. Silicon-carbon negative electrode materials have advantages such as higher theoretical specific capacity, low delithiation potential, environmental friendliness, abundant reserves, and low cost, and have become highly concerned high-specific energy lithium-ion battery negative electrode materials. Therefore, manufacturing lithium-ion batteries through ternary positive electrode materials and silicon-carbon negative electrode materials is an effective means to improve the specific energy of lithium-ion batteries. However, at present, this type of lithium-ion battery often has a short cycle life. Through research, it is found that one of the main factors limiting the cycle life of ternary positive electrode silicon-carbon negative electrode lithium-ion batteries is that conventional lithium-ion battery electrolytes have poor matching with silicon-carbon negative electrodes. As the cycle progresses, silicon is easy to expand and break, consuming electrolytes, thereby causing the battery capacity to drop rapidly. Therefore, it is necessary to develop a new electrolyte to solve the problem of short cycle life of ternary positive electrode silicon-carbon negative electrode lithium-ion batteries. Summary of the invention
[0004] The technical problem to be solved by the present invention is: to overcome the shortcomings of the prior art, to provide an electrolyte for a ternary positive electrode silicon-carbon negative electrode lithium ion battery and its application, and to form a high-quality SEI film on the surface of graphite and silicon by regulating the components of the electrolyte and the distribution ratio of each component, so as to inhibit the volume expansion of silicon during the cycle process, thereby achieving the purpose of extending the cycle life of the ternary positive electrode silicon-carbon negative electrode lithium ion battery.
[0005] The technical solution of the present invention is:
[0006] On the one hand, the present invention provides an electrolyte for a ternary positive electrode silicon-carbon negative electrode lithium ion battery, comprising a mother solution and additives, wherein the additives include a positive electrode film-forming agent, a negative electrode composite film-forming agent and a coating agent, wherein the positive electrode film-forming agent is LiDFOB, and the mass of the positive electrode film-forming agent is 0.6-1% of the mass of the mother solution; the negative electrode composite film-forming agent is fluoroethylene carbonate (FEC) and lithium difluorophosphate (LiPO2F2) in a mass ratio of (11-33):1, and the mass of the negative electrode composite film-forming agent is 9-14% of the mass of the mother solution; the coating agent is N,N-methylenebisacrylamide (MBA) and propenyl-1,3-sultone (PST) in a mass ratio of 1:(2-2.5), and the mass of the coating agent is 0.5-1% of the mass of the mother solution.
[0007] In the present invention, if the amount of LiDFOB added is too much, the boron-containing oxide film formed on the positive electrode will be too thick or too dense, resulting in too high impedance of lithium insertion and extraction at the positive electrode, affecting the cycle performance of the battery; if the amount of LiDFOB added is too low, the boron-containing oxide film formed will be too thin or too loose, and the effect of preventing the electrolyte solvent from being oxidized by the positive electrode and resisting the anisotropic stress of the positive electrode material is limited, and it will not play a role in extending the cycle performance of the positive electrode or the battery. In the negative electrode composite film-forming agent, if the mass ratio of FEC and LiPO2F2 is too large, the density of the formed SEI film is poor; if the mass ratio of the two is too low, the ion permeability of the formed SEI film becomes poor, resulting in too high impedance of the negative electrode. If the amount of negative electrode composite film-forming agent added is too much, the film on graphite is too dense, and the impedance of lithium insertion and extraction on graphite is too large; if the amount of LiDFOB added is too low, the film on silicon is discontinuous and the thickness is insufficient, and the purpose of inhibiting the free expansion of silicon is not achieved. The two monomers MBA and PST in the coating agent initiate polymerization through carbon anions in the negative electrode. Setting the mass ratio of the two to 1: (2-2.5) can ensure that the two can fully react. In addition, if the amount of coating agent added is too low, the formed polymer will have a weak fixation effect on the negative electrode active material; if the amount added is too much, it will reduce the transmission of ions on the interface, causing the battery polarization internal resistance to increase.
[0008] Preferably, the solvent of the mother solution is DMC, EC and EMC.
[0009] Preferably, the volume ratio of DMC, EC and EMC is 1:(1-1.5):(1-2).
[0010] Preferably, the solute of the mother liquor is LiPF6.
[0011] Preferably, the concentration of LiPF6 in the mother liquor is 0.8-1.2 mol / L.
[0012] On the other hand, the present invention provides an application of the electrolyte of the above-mentioned ternary positive silicon-carbon negative lithium ion battery. The electrolyte is poured into the dry battery, firstly, it is allowed to stand at 15-20°C for 10-12h to allow the electrolyte to fully infiltrate the pole piece so that the battery capacity can be fully utilized. If the standing temperature is too low, the infiltration speed is slow, and if the standing temperature is too high, the coating agent monomer will be polymerized. If the standing time is too short, the deep inside of the pole piece cannot be infiltrated, and if the standing time is too long, it will affect the battery production cycle; then at 15-2 At 0℃, the current density is controlled to be 0.01-0.03C, and the constant current charging is performed for 3-5h. If the current density is too low, the time is too short or the temperature is too low, the quality of the positive electrode film formation will be affected, and the film will be too thin, discontinuous or loose, which will have a poor effect on extending the positive electrode or battery cycle performance. If the current density is too high, the time is too long or the temperature is too high, the film will be too thick or too dense, and the positive electrode lithium insertion and extraction impedance will be too large, affecting the battery cycle performance; then the current density is controlled to be 0.04-0.0 at 21-25℃. 6C, constant current charging for 6-8h. If the temperature is too low, the current density is too low or the constant current charging time is too short, the SEI film will not form or the SEI film will be discontinuous. If the temperature is too high, the current density is too high or the constant current charging time is too long, the film will be too thick, the battery polarization will increase, and the heat generated during the charge and discharge process will increase, affecting the cycle performance. Finally, the current density is controlled at 0.08-0.12C at 26-35℃, and the constant current charging is performed for 8-12h. If the current density is too low, the concentration of carbon anions in the negative electrode is low, which is not conducive to the introduction of If the current density is too high and the polymerization rate is too fast, the polymer will not have time to rearrange on the surface of the silicon-carbon negative electrode, and the coating effect on the negative electrode active material will be poor. If the temperature is too low, the monomer activity is poor, which is not conducive to polymerization. If the temperature is too high, it will cause the monomer to polymerize in the electrolyte, resulting in an increase in the viscosity of the electrolyte, a decrease in ionic conductivity, and failure to inhibit the expansion of the negative electrode and fix the negative electrode active material. If the polymerization time is too short, the monomer in the electrolyte cannot completely diffuse to the negative electrode interface for polymerization.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] Since the voltage of the ternary positive electrode silicon-carbon negative electrode lithium ion battery is relatively high, above 4.2V, the positive electrode has strong oxidation, and the solvent in the electrolyte is easily oxidized, which affects the battery cycle performance. After the positive electrode film-forming agent LiDFOB is added to the present invention, LiDFOB decomposes under the oxidation action of the positive electrode, and a layer of oxide film containing boron can be formed on the surface of the positive electrode active material. This film can reduce the speed of oxidation and decomposition of the solvent in the electrolyte at the positive electrode, slow down the loss rate of the electrolyte, and extend the effective period of the electrolyte; on the other hand, the boron-containing oxide film can resist the anisotropic stress of the positive electrode active material during the charge and discharge process to a certain extent, slow down the pulverization of the positive electrode material, and thus improve the cycle performance of the positive electrode. At the same time, the negative electrode composite film-forming agent FEC and LiPO2F2 in the present invention cooperate to form a better quality SEI film, and the formed SEI film has stable performance and good lithium ion permeability; the coating agents MBA and PST form a high molecular polymer coating layer on the negative electrode surface, which has good electrolyte permeability, and the resistance of the electrolyte through the high molecular polymer coating layer is very small, which not only does not affect the electrochemical performance of the battery, but also is beneficial to the cycle performance of the battery. In summary, the present invention forms a high-quality SEI film on the silicon surface by regulating the electrolyte components and the distribution ratio of each component, which can inhibit the volume expansion of silicon during the cycle process, thereby achieving the purpose of extending the cycle life of the ternary positive silicon-carbon negative lithium ion battery. DETAILED DESCRIPTION
[0015] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0016] The performance of the electrolytes of the following embodiments and comparative examples was tested by assembling a 5.5Ah ternary positive silicon-carbon negative lithium-ion battery. The positive electrode material model was M2-C2, the electrode piece size was 81mm×96mm, and the double-sided coating surface density was 42mg / cm 2 The content of positive electrode active material in the coating is 95wt.%, and the compaction density of the coating is 3.2g / cm 3 ; The negative electrode material is SC-500, the electrode size is 83mm×98mm, and the double-sided coating surface density is 20mg / cm 2 The content of negative electrode active material in the coating is 95wt.%, and the compaction density of the coating is 1.55g / cm 3 The battery structure is 10 positive and 11 negative. The cycle performance test method is: 0.5C constant current charging to 4.25V, then constant voltage charging to 0.05C, and then 1C constant current discharge to 2.75V.
[0017] Example 1
[0018] The electrolyte of the ternary positive silicon-carbon negative lithium ion battery of this embodiment includes a mother liquor and additives, wherein the solvent of the mother liquor is DMC, EC and EMC in a volume ratio of 1:1:1, and the solute of the mother liquor is 0.8 mol / L LiPF6; the additives include a positive electrode film-forming agent, a negative electrode composite film-forming agent and a coating agent, the positive electrode film-forming agent is LiDFOB, and the positive electrode film-forming agent accounts for 0.6% of the mother liquor mass; the negative electrode composite film-forming agent is FEC and LiPO2F2 in a mass ratio of 11:1, and the negative electrode composite film-forming agent accounts for 9% of the mother liquor mass; the coating agent is MBA and PST in a mass ratio of 1:2, and the coating agent accounts for 0.5% of the mother liquor mass.
[0019] The method of using the electrolyte of this embodiment is as follows:
[0020] S1: inject the electrolyte into the dry cell and place it at 15℃ for 12h;
[0021] S2 was charged at a constant current of 0.01C at 15°C for 5 h to form a positive electrode film;
[0022] S3 was charged at a constant current of 0.04C at 21°C for 8 h to polymerize and coat the negative electrode;
[0023] S4 controlled the current density to 0.08C at 26°C and charged at constant current for 12 hours to form a negative electrode film.
[0024] The 5.5Ah ternary positive silicon-carbon negative lithium ion battery assembled in this embodiment was cycled 300 times at 25°C, and the capacity retention rate was 94.4%.
[0025] Example 2
[0026] The electrolyte of the ternary positive silicon-carbon negative lithium ion battery of this embodiment includes a mother liquor and additives, wherein the solvent of the mother liquor is DMC, EC and EMC in a volume ratio of 1:1.25:1.5, and the solute of the mother liquor is 1 mol / L LiPF6; the additives include a positive electrode film-forming agent, a negative electrode composite film-forming agent and a coating agent, the positive electrode film-forming agent is LiDFOB, and the positive electrode film-forming agent accounts for 1% of the mother liquor mass; the negative electrode composite film-forming agent is FEC and LiPO2F2 in a mass ratio of 33:1, and the negative electrode composite film-forming agent accounts for 14% of the mother liquor mass; the coating agent is MBA and PST in a mass ratio of 1:2.25, and the coating agent accounts for 1% of the mother liquor mass.
[0027] The method of using the electrolyte of this embodiment is as follows:
[0028] S1: inject the electrolyte into the dry cell and place it at 20℃ for 10h;
[0029] S2 was charged at a constant current of 0.03C at 20°C for 3 h to form a positive electrode film;
[0030] S3 was charged at a constant current of 0.06C at 25°C for 6 h to polymerize and coat the negative electrode;
[0031] S4 controlled the current density to 0.12C at 35°C and charged at constant current for 8 hours to form a negative electrode film.
[0032] The 5.5Ah ternary positive silicon-carbon negative lithium ion battery assembled in this embodiment was cycled 300 times at 25°C, and the capacity retention rate was 94.6%.
[0033] Example 3
[0034] The electrolyte of the ternary positive silicon-carbon negative lithium ion battery of this embodiment includes a mother liquor and additives, wherein the solvent of the mother liquor is DMC, EC and EMC in a volume ratio of 1:1.5:2, and the solute of the mother liquor is 1.2 mol / L LiPF6; the additives include a positive electrode film-forming agent, a negative electrode composite film-forming agent and a coating agent, the positive electrode film-forming agent is LiDFOB, and the positive electrode film-forming agent accounts for 0.8% of the mother liquor mass; the negative electrode composite film-forming agent is FEC and LiPO2F2 in a mass ratio of 22:1, and the negative electrode composite film-forming agent accounts for 12% of the mother liquor mass; the coating agent is MBA and PST in a mass ratio of 1:2.5, and the coating agent accounts for 0.8% of the mother liquor mass.
[0035] The method of using the electrolyte of this embodiment is as follows:
[0036] S1: inject the electrolyte into the dry cell and place it at 18℃ for 11h;
[0037] S2 was charged at a constant current of 0.02C at 18°C for 4 h to form a positive electrode film;
[0038] S3 was charged at a constant current of 0.05C at 23°C for 7 h to polymerize and coat the negative electrode;
[0039] S4 was charged at a constant current of 0.1C at 30°C for 10 h to form a negative electrode film.
[0040] The 5.5Ah ternary positive silicon-carbon negative lithium ion battery assembled in this embodiment was cycled 300 times at 25°C, and the capacity retention rate was 94.3%.
[0041] Comparative Example 1
[0042] The difference from Example 1 is that the mass of LiDFOB accounts for 1.5% of the mass of the mother liquor.
[0043] The 5.5Ah ternary positive silicon-carbon negative lithium ion battery assembled in Comparative Example 1 was cycled 300 times at 25°C, and the capacity retention rate was 92.7%.
[0044] By comparing Example 1 and Comparative Example 1, it can be seen that when the amount of positive electrode film-forming agent LiDFOB is too much, the 300 cycle capacity retention rate of the ternary positive electrode silicon-carbon negative electrode lithium ion battery will be significantly reduced. This is because when the amount of LiDFOB added is too much, the boron-containing oxide film formed on the positive electrode is too thick or too dense, resulting in too high positive electrode lithium insertion and extraction impedance, increased battery polarization, and reduced cycle performance.
[0045] Comparative Example 2
[0046] The difference from Example 1 is that the mass of LiDFOB accounts for 0.4% of the mass of the mother liquor.
[0047] The 5.5Ah ternary positive silicon-carbon negative lithium ion battery assembled in Comparative Example 2 was cycled 300 times at 25°C, and the capacity retention rate was 91.6%.
[0048] By comparing Example 1 and Comparative Example 2, it can be seen that when the amount of positive electrode film-forming agent LiDFOB added is too little, the 300 cycle capacity retention rate of the ternary positive electrode silicon-carbon negative electrode lithium ion battery will be significantly reduced. This is because when the amount of LiDFOB added is too little, the boron-containing oxide film formed on the positive electrode is too thin or too loose. On the one hand, the electrolyte solvent is oxidized on the positive electrode, and the electrolyte gradually decreases; on the other hand, the boron-containing oxide film on the positive electrode weakens the resistance to the anisotropic stress of the positive electrode material, and the positive electrode active material is pulverized, resulting in a decrease in cycle performance.
[0049] Comparative Example 3
[0050] The difference from Example 1 is that in step S1, the standing temperature is 30°C.
[0051] The 5.5Ah ternary positive silicon-carbon negative lithium ion battery assembled in Comparative Example 3 was cycled 300 times at 25°C, and the capacity retention rate was 93.2%.
[0052] By comparing Example 1 and Comparative Example 3, it can be seen that if the standing temperature in step S1 is too high, the 300 cycle capacity retention rate of the ternary positive silicon-carbon negative lithium ion battery will be significantly reduced. This is because when the standing temperature is too high, MBA and PST in the coating agent will spontaneously polymerize in the electrolyte to generate polymer substances, which will increase the viscosity of the electrolyte and ultimately reduce the ionic conductivity of the electrolyte, thereby reducing the cycle performance of the battery.
[0053] Comparative Example 4
[0054] The difference from Example 1 is that in step S2, the current density is 0.005C and the constant current charging time is 2h.
[0055] The 5.5Ah ternary positive silicon-carbon negative lithium ion battery assembled in Comparative Example 4 was cycled 300 times at 25°C, and the capacity retention rate was 91.3%.
[0056] By comparing Example 1 and Comparative Example 4, it can be seen that if the current density in step S2 is too low and the constant current charging time is too short, the 300 cycle capacity retention rate of the ternary positive electrode silicon-carbon negative electrode lithium ion battery will be significantly reduced. This is because at a lower current density and a shorter constant current charging time, the boron-containing oxide film formed on the positive electrode will be too thin, discontinuous or loose, which will prevent the electrolyte from being oxidized and decomposed by the positive electrode and reduce the ability to resist the anisotropic stress of the positive electrode material. Finally, the battery will have a reduced cycle performance due to lack of electrolyte and pulverization of active substances.
[0057] Comparative Example 5
[0058] The difference from Example 1 is that in step S2, the constant current charging temperature is 10°C.
[0059] The 5.5Ah ternary positive silicon-carbon negative lithium ion battery assembled in Comparative Example 5 was cycled 300 times at 25°C, and the capacity retention rate was 91.6%.
[0060] By comparing Example 1 and Comparative Example 5, it can be seen that if the constant current charging temperature in step S2 is too low, the 300 cycle capacity retention rate of the ternary positive electrode silicon-carbon negative electrode lithium ion battery will be significantly reduced. This is because at a lower constant current charging temperature, the electrochemical activity of LiDFOB is reduced, the ability and quality of the oxide film formed on the positive electrode are reduced, and the oxide film formed is too thin, discontinuous or loose, which has a weak effect on extending the cycle performance of the positive electrode or battery.
[0061] Comparative Example 6
[0062] The difference from Example 1 is that in step S2, the current density is 0.05C and the constant current charging time is 8h.
[0063] The 5.5Ah ternary positive silicon-carbon negative lithium-ion battery assembled in Comparative Example 6 was cycled 300 times at 25°C, and the capacity retention rate was 92.5%.
[0064] By comparing Example 1 and Comparative Example 6, it can be seen that if the current density in step S2 is too high and the constant current charging time is too long, the 300 cycle capacity retention rate of the ternary positive silicon-carbon negative lithium ion battery will be significantly reduced. This is because when the current density is too high and the constant current charging time is too long, the boron-containing oxide film formed on the positive electrode is too thick or too dense, resulting in too high positive electrode lithium insertion and extraction impedance, increased battery polarization, and reduced cycle performance.
[0065] Comparative Example 7
[0066] The difference from Example 1 is that in step S2, the constant current charging temperature is 25°C.
[0067] The 5.5Ah ternary positive silicon-carbon negative lithium ion battery assembled in Comparative Example 7 was cycled 300 times at 25°C, and the capacity retention rate was 92.3%.
[0068] By comparing Example 1 and Comparative Example 7, it can be seen that if the constant current charging temperature in step S2 is too high, the 300 cycle capacity retention rate of the ternary positive electrode silicon-carbon negative electrode lithium ion battery will be significantly reduced. This is because when the constant current charging temperature is too high, the boron-containing oxide film formed on the positive electrode is too thick or too dense, resulting in a decrease in cycle performance.
[0069] Comparative Example 8
[0070] The difference from Example 1 is that in the negative electrode composite film-forming agent, the mass ratio of FEC to LiPO2F2 is 44:1.
[0071] The 5.5Ah ternary positive silicon-carbon negative lithium ion battery assembled in Comparative Example 8 was cycled 300 times at 25°C, and the capacity retention rate was 91.5%.
[0072] By comparing Example 1 and Comparative Example 8, it can be seen that when the mass ratio of FEC and LiPO2F2 in the negative electrode composite film-forming agent is too large, the 300 cycle capacity retention rate of the ternary positive electrode silicon-carbon negative electrode lithium ion battery will be significantly reduced. This is because when the mass ratio of FEC and LiPO2F2 in the negative electrode composite film-forming agent is too large, the SEI film formed by FEC on the negative electrode has poor compactness, which affects the cycle life of the battery.
[0073] Comparative Example 9
[0074] The difference from Example 1 is that in the negative electrode composite film-forming agent, the mass ratio of FEC to LiPO2F2 is 8:1.
[0075] The 5.5Ah ternary positive silicon-carbon negative lithium ion battery assembled in Comparative Example 9 was cycled 300 times at 25°C, and the capacity retention rate was 91.2%.
[0076] By comparing Example 1 and Comparative Example 9, it can be seen that if the mass ratio of FEC and LiPO2F2 in the negative electrode composite film-forming agent is too low, the 300 cycle capacity retention rate of the ternary positive electrode silicon-carbon negative electrode lithium ion battery will be significantly reduced. This is because when the mass ratio of FEC and LiPO2F2 in the negative electrode composite film-forming agent is too low, the density of the LiPO2F2 film is too high, the SEI film formed on the negative electrode is too dense, and the ion permeability becomes poor, resulting in a large internal resistance of the battery, which affects the cycle life of the battery.
[0077] Comparative Example 10
[0078] The difference from Example 1 is that the mass of the negative electrode composite film-forming agent is 18% of the mass of the mother solution.
[0079] The 5.5Ah ternary positive silicon-carbon negative lithium ion battery assembled in Comparative Example 10 was cycled 300 times at 25°C, and the capacity retention rate was 92.2%.
[0080] By comparing Example 1 and Comparative Example 10, it can be seen that excessive addition of the negative electrode composite film-forming agent will lead to a significant decrease in the 300 cycle capacity retention rate of the ternary positive electrode silicon-carbon negative electrode lithium ion battery. This is because when too much negative electrode composite film-forming agent is added, the film is too dense on the graphite in the silicon-carbon negative electrode, the lithium insertion and extraction impedance on the graphite is too large, and more heat is generated, which affects the battery cycle life.
[0081] Comparative Example 11
[0082] The difference from Example 1 is that the mass of the negative electrode composite film-forming agent is 6% of the mass of the mother solution.
[0083] The 5.5Ah ternary positive silicon-carbon negative lithium-ion battery assembled in Comparative Example 11 was cycled 300 times at 25°C, and the capacity retention rate was 91.4%.
[0084] By comparing Example 1 and Comparative Example 11, it can be seen that too little addition of the negative electrode composite film-forming agent will result in a significant decrease in the 300 cycle capacity retention rate of the ternary positive electrode silicon-carbon negative electrode lithium ion battery. This is because when too little addition of the negative electrode composite film-forming agent is added, the film formed on the silicon in the silicon-carbon negative electrode is too thin and discontinuous, and the expansion of silicon cannot be suppressed, resulting in repeated rupture and regeneration of the SEI film on the silicon, consuming lithium ions in the electrolyte and affecting the battery cycle life.
[0085] Comparative Example 12
[0086] The difference from Example 1 is that in step S3, the current density is 0.02C and the constant current charging time is 4h.
[0087] The 5.5Ah ternary positive silicon-carbon negative lithium ion battery assembled in Comparative Example 12 was cycled 300 times at 25°C, and the capacity retention rate was 90.4%.
[0088] By comparing Example 1 and Comparative Example 12, it can be seen that if the current density in step S3 is too low and the constant current charging time is too short, the 300 cycle capacity retention rate of the ternary positive silicon-carbon negative lithium ion battery will be significantly reduced. This is because if the current density in step S3 is too low and the constant current charging time is too short, the SEI film cannot be formed or the SEI film is discontinuous, affecting the cycle performance of the battery.
[0089] Comparative Example 13
[0090] The difference from Example 1 is that in step S3, the constant current charging temperature is 15°C.
[0091] The 5.5Ah ternary positive silicon-carbon negative lithium ion battery assembled in Comparative Example 13 was cycled 300 times at 25°C, and the capacity retention rate was 90.8%.
[0092] By comparing Example 1 and Comparative Example 13, it can be seen that if the constant current charging temperature in step S3 is too low, the 300 cycle capacity retention rate of the ternary positive silicon-carbon negative lithium ion battery will be significantly reduced. This is because when the constant current charging temperature in step S3 is too low, the electrochemical activity of the negative electrode composite film-forming agent is low, and the SEI film cannot be formed on the negative electrode surface or the SEI film is discontinuous, which affects the cycle performance of the battery.
[0093] Comparative Example 14
[0094] The difference from Example 1 is that in step S3, the current density is 0.08C and the constant current charging time is 10 h.
[0095] The 5.5Ah ternary positive silicon-carbon negative lithium ion battery assembled in Comparative Example 14 was cycled 300 times at 25°C, and the capacity retention rate was 91.5%.
[0096] By comparing Example 1 and Comparative Example 14, it can be seen that if the current density in step S3 is too high and the constant current charging time is too long, the 300 cycle capacity retention rate of the ternary positive silicon-carbon negative lithium ion battery will be significantly reduced. This is because if the current density in step S3 is too high and the constant current charging time is too long, the film will be too thick, the battery polarization will increase, and the heat generated during the charge and discharge process will increase, affecting the battery cycle performance.
[0097] Comparative Example 15
[0098] The difference from Example 1 is that in step S3, the constant current charging temperature is 30°C.
[0099] The 5.5Ah ternary positive silicon-carbon negative lithium ion battery assembled in Comparative Example 15 was cycled 300 times at 25°C, and the capacity retention rate was 92.6%.
[0100] By comparing Example 1 and Comparative Example 15, it can be seen that if the constant current charging temperature in step S3 is too high, the 300 cycle capacity retention rate of the ternary positive silicon-carbon negative lithium ion battery will be significantly reduced. This is because if the constant current charging temperature in step S3 is too high, the film will be too thick, the battery polarization will increase, and the heat generated during the charge and discharge process will increase, affecting the battery cycle performance.
[0101] Comparative Example 16
[0102] The difference from Example 1 is that the mass of the coating agent is 0.2% of the mass of the mother solution.
[0103] The 5.5Ah ternary positive silicon-carbon negative lithium ion battery assembled in Comparative Example 16 was cycled 300 times at 25°C, and the capacity retention rate was 91.5%.
[0104] By comparing Example 1 and Comparative Example 16, it can be seen that if the amount of coating agent added is too low, the 300 cycle capacity retention rate of the ternary positive electrode silicon-carbon negative electrode lithium ion battery will be significantly reduced. This is because when the amount of coating agent added is too low, the polymer layer formed is thinner, the fixation effect on the negative electrode active material is weaker, and the effect of inhibiting the expansion of the negative electrode is limited, which affects the battery cycle performance.
[0105] Comparative Example 17
[0106] The difference from Example 1 is that the mass of the coating agent is 2% of the mass of the mother solution.
[0107] The 5.5Ah ternary positive silicon-carbon negative lithium ion battery assembled in Comparative Example 17 was cycled 300 times at 25°C, and the capacity retention rate was 92.1%.
[0108] By comparing Example 1 with Comparative Example 17, it can be seen that when the amount of coating agent added is too much, the 300 cycle capacity retention rate of the ternary positive silicon-carbon negative lithium ion battery will be significantly reduced. This is because when the amount of coating agent added is too much, the polymer layer formed is thicker, the ion transmission capacity on the interface is reduced, resulting in an increase in the polarization internal resistance of the battery, affecting the battery cycle performance.
[0109] Comparative Example 18
[0110] The difference from Example 1 is that in step S4, the current density is 0.04C.
[0111] The 5.5Ah ternary positive silicon-carbon negative lithium ion battery assembled in Comparative Example 18 was cycled 300 times at 25°C, and the capacity retention rate was 91.6%.
[0112] By comparing Example 1 and Comparative Example 18, it can be seen that if the current density in step S4 is too low, the 300 cycle capacity retention rate of the ternary positive electrode silicon-carbon negative electrode lithium ion battery will be significantly reduced. This is because when the current density in step S4 is too low, the concentration of carbon anions formed in the negative electrode is low, which is not conducive to initiating the polymerization reaction of the coating agent, the polymerization is insufficient, and the effect of fixing the negative electrode active material is weak, which affects the battery cycle performance.
[0113] Comparative Example 19
[0114] The difference from Example 1 is that in step S4, the current density is 0.15C.
[0115] The 5.5Ah ternary positive silicon-carbon negative lithium ion battery assembled in Comparative Example 19 was cycled 300 times at 25°C, and the capacity retention rate was 92.1%.
[0116] By comparing Example 1 and Comparative Example 19, it can be seen that if the current density in step S4 is too high, the 300 cycle capacity retention rate of the ternary positive electrode silicon-carbon negative electrode lithium ion battery will be significantly reduced. This is because when the current density in step S4 is too high, the concentration of carbon anions formed in the negative electrode is high, the polymerization reaction rate of the coating agent is too fast, and the polymer has no time to rearrange on the surface of the silicon-carbon negative electrode, resulting in poor coating effect on the negative electrode active material, which affects the battery cycle performance.
[0117] Comparative Example 20
[0118] The difference from Example 1 is that in step S4, the constant current charging temperature is 20°C.
[0119] The 5.5Ah ternary positive silicon-carbon negative lithium ion battery assembled in Comparative Example 20 was cycled 300 times at 25°C, and the capacity retention rate was 91.8%.
[0120] By comparing Example 1 and Comparative Example 20, it can be seen that if the constant current charging temperature in step S4 is too low, the 300 cycle capacity retention rate of the ternary positive silicon-carbon negative lithium ion battery will be significantly reduced. This is because when the constant current charging temperature in step S4 is too low, the monomer activity is poor, which is not conducive to the polymerization reaction and affects the battery cycle performance.
[0121] Comparative Example 21
[0122] The difference from Example 1 is that in step S4, the constant current charging temperature is 45°C.
[0123] The 5.5Ah ternary positive silicon-carbon negative lithium-ion battery assembled in Comparative Example 21 was cycled 300 times at 25°C, and the capacity retention rate was 90.8%.
[0124] By comparing Example 1 and Comparative Example 21, it can be seen that if the constant current charging temperature in step S4 is too high, the 300 cycle capacity retention rate of the ternary positive silicon-carbon negative lithium ion battery will be significantly reduced. This is because when the constant current charging temperature in step S4 is too high, it will cause the monomers to polymerize in the electrolyte liquid phase, resulting in an increase in the viscosity of the electrolyte body, a decrease in ionic conductivity, and the inability to inhibit the expansion of the negative electrode and fix the negative electrode active material, affecting the battery cycle performance.
Claims
1. An electrolyte for a ternary positive electrode silicon-carbon negative electrode lithium-ion battery, characterized in that: The invention comprises a mother solution and additives, wherein the additives comprise a positive electrode film-forming agent, a negative electrode composite film-forming agent and a coating agent, wherein the positive electrode film-forming agent is LiDFOB, and the mass of the positive electrode film-forming agent is 0.6-1% of the mass of the mother solution; the negative electrode composite film-forming agent is fluoroethylene carbonate and lithium difluorophosphate in a mass ratio of (11-33):1, and the mass of the negative electrode composite film-forming agent is 9-14% of the mass of the mother solution; the coating agent is N,N-methylenebisacrylamide and acryl-1,3-sulfonic acid lactone in a mass ratio of 1:(2-2.5), and the mass of the coating agent is 0.5-1% of the mass of the mother solution.
2. The electrolyte of the ternary positive silicon-carbon negative lithium ion battery according to claim 1, characterized in that: The solvents of the mother liquor are DMC, EC and EMC.
3. The electrolyte of the ternary positive electrode silicon-carbon negative electrode lithium ion battery according to claim 2, characterized in that: The volume ratio of DMC, EC and EMC is 1:(1-1.5):(1-2).
4. The electrolyte of the ternary positive silicon-carbon negative lithium ion battery according to claim 1, characterized in that: The solute of the mother liquor is LiPF6.
5. The electrolyte of the ternary positive silicon-carbon negative lithium ion battery according to claim 4, characterized in that: The concentration of LiPF6 in the mother liquor is 0.8-1.2 mol / L.
6. The use of the electrolyte of the ternary positive silicon-carbon negative lithium ion battery as claimed in claim 1, characterized in that: Pour the electrolyte into the dry cell, first let it stand at 15-20℃ for 10-12h; then control the current density to 0.01-0.03C at 15-20℃, and charge at constant current for 3-5h; then control the current density to 0.04-0.06C at 21-25℃, and charge at constant current for 6-8h; finally control the current density to 0.08-0.12C at 26-35℃, and charge at constant current for 8-12h.
Citation Information
Patent Citations
Lithium ion battery electrolyte applicable to silicon carbon negative electrode and resistant to high voltage
CN106848399A
Preparation method of gel polymer electrolyte with double-network structure
CN112679660A